Colour and surface fluorescence development and their relationship with Maillard reaction markers as influenced by structural changes during cornflakes production - Farroni, Abel Eduardo (2012)
The aim of this work was to study colour and surface fluorescence development in relation to the chemical markers for the Maillard reaction at the cooking, flaking and toasting stages of cornflake production process. Colour was measured by a calibrated computer vision system. Surface fluorescence was measured on compressed samples. Aqueous extracted Maillard reaction markers (hydroxymethylfurfural, carboxymethyl-lysine, absorbance at 420 nm and total fluorescence) were measured on protease hydrolyzed samples. Sample microstructure was observed by scanning electron microscopy. During cooking the colour coordinates L⁄ and b⁄ decreased and a⁄ increased. After flaking, the samples appeared lighter, while the pigment concentration, fluorescence and hydroxymethylfurfural did not change. Toasting generated bubbles in the matrix and L⁄ apparently increased, although brown pigment concentration increased. Pigment concentration did not correlate with surface colour due to the destruction or generation of interfaces. Surface and microstructure effects can be avoided by milling and compressing the samples.